2015
DOI: 10.3389/fendo.2015.00117
|View full text |Cite
|
Sign up to set email alerts
|

Familial Non-Medullary Thyroid Cancer Represents an Independent Risk Factor for Increased Cancer Aggressiveness: A Retrospective Analysis of 74 Families

Abstract: ObjectivesTo assess whether familial non-medullary thyroid cancer (FNMTC) represents an independent risk factor for increased aggressiveness of the tumor, as concern as the clinical presentation and the long-term follow-up in respect of sporadic differentiated thyroid cancer (SDTC).DesignRetrospective study; 1976–2014.Patients and MethodsSeventy-four FNMTC families (151 affected individuals): family relationship and number of affected family members were evaluated. Clinical and histopathological features and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 25 publications
6
39
1
Order By: Relevance
“…33 Recent data suggest that FNMTC is more likely to present with multifocal or advanced disease and is more likely to recur after resection. 34,35 While some studies have suggested benefit with US screening in these patients, 36 there are no current recommendations for thyroid screening in patients with suspected FNMTC. Annual physical exam findings should continue to guide work-up.…”
Section: Familial Non-mtcmentioning
confidence: 99%
“…33 Recent data suggest that FNMTC is more likely to present with multifocal or advanced disease and is more likely to recur after resection. 34,35 While some studies have suggested benefit with US screening in these patients, 36 there are no current recommendations for thyroid screening in patients with suspected FNMTC. Annual physical exam findings should continue to guide work-up.…”
Section: Familial Non-mtcmentioning
confidence: 99%
“…Many groups report no difference in age between familial and sporadic cases [52, 53, 5558]. In contrast, other groups report a lower average age in familial disease [31, 54].…”
Section: Clinico-pathological Features Of Familial Non-medullary Thyrmentioning
confidence: 99%
“…In terms of the pathological presentation of disease, many groups have shown that familial disease is associated with increased rates of multicentric papillary cancers [19, 57, 58, 61]. Although not all groups have found this to be statistically significant due to the already high rate of multifocality in sporadic NMTC [52], the majority of series report rates of multicentricity of approximately 50% in patients with a family history versus 30–40% in sporadic cases [50, 5356, 59, 62, 63].…”
Section: Clinico-pathological Features Of Familial Non-medullary Thyrmentioning
confidence: 99%
See 2 more Smart Citations